Analisa Harga Pokok Produksi untuk Mengurangi Biaya Produksi pada Usaha Ayam Goreng Kanaya dengan metode Target Costing - Mukhammad Ubaidillah; Ribangun Bamban Jakaria (JURNAL ILMIAH RESEARCH STUDENT, 2024)
In this research, which is used as a reference for determining product sales to achieve the level of profit expected by the company, the researcher analyzes using Target Costing where the method used can manage costs to achieve cost efficiency and the company's goals in gaining profits. This research aims to determine the impact that obtained by the company after applying the Target Costing method. This research is a descriptive quantitative research. In the results of this research, it is known that the difference in the increase in gross profit is IDR. 1,602,000. It can be said that companies gain more profits by implementing the Target Costing Method because it can reduce costs more efficiently